BDNF-producing, amyloid β-specific CD4 T cells as targeted drug-delivery vehicles in Alzheimer's diseaseResearch in context - Ekaterina Eremenko; Kritika Mittal; Omer Berner; Nikita Kamenetsky; Anna Nemirovsky; Yehezqel Elyahu; Alon Monsonego (EBioMedicine, 2019)
Background: The delivery of therapeutic proteins to selected sites within the central nervous system (CNS) parenchyma is a major challenge in the treatment of various neurodegenerative disorders. As brain-derived neurotrophic factor (BDNF) is reduced in the brain of people with Alzheimer's disease (AD) and its administration has shown promising therapeutic effects in mouse model of the disease, we generated a novel platform for T cell-based BDNF delivery into the brain parenchyma. Methods: We generated amyloid beta-protein (Aβ)-specific CD4 T cells (Aβ-T cells), genetically engineered to express BDNF, and injected them intracerebroventricularly into the 5XFAD mouse model of AD. Findings: The BDNF-secreting Aβ-T cells migrated efficiently to amyloid plaques, where they significantly increased the levels of BDNF, its receptor TrkB, and various synaptic proteins known to be reduced in AD. Furthermore, the injected mice demonstrated reduced levels of beta-secretase 1 (BACE1)—a protease essential in the cleavage process of the amyloid precursor protein—and ameliorated amyloid pathology and inflammation within the brain parenchyma. Interpretation: A T cell-based delivery of proteins into the brain can serve as a platform to modulate neurotoxic inflammation and to promote neuronal repair in neurodegenerative diseases. Keywords: Cell-based delivery, CD4 T cell, BDNF, CNS, Brain, Alzheimer's disease, Amyloid plaques, Targeted drug delivery